Effect of different toothpastes on permeability and roughness of eroded dentin - Ramos, Fernanda S. S. [UNESP]; Delbem, Alberto C. B. [UNESP]; Dos Santos, Paulo H. [UNESP]; Moda, Mariana D. [UNESP]; Briso, André L. F. [UNESP]; Fagundes, Ticiane C. [UNESP] (Sociedad Argentina de Investigacion Odontologica, 2022)
Dentin hypersensitivity (DH) is characterized by rapid, acute pain arising from exposed dental tubules. Aim: the aim of this study was to evaluate the roughness, tubule occlusion, and permeability of eroded dentin brushed with different toothpastes. Materials and Method: ninety bovine teeth were cut into blocks. Thirty hemifaces were protected with varnish and the other sixty were submitted to permeability tests. Specimens were divided into groups according to the dentifrices: without fluoride (WF), sodium fluoride (NaF), and stannous fluoride (SnF2). The blocks were subjected to a 5-day erosive-abrasive protocol. Surface roughness and dentinal tubule occlusion (n=10) were assessed for both control and test hemifaces of the same sample along with permeability analysis (n=20). Two-way RM ANOVA and Tukey’s post-hoc test were performed (p≤0.05). Results: NaF and SnF2 presented higher roughness than WF. The number of open tubules was higher in WF. Permeability was higher in SnF2, but there was no significant difference between WF and NaF. Conclusions: both fluoride toothpastes occluded dentinal tubules and increased roughness. NaF toothpaste promoted greater decrease in dentin permeability.
Efeito de diferentes cremes dentais na permeabilidade e rugosidade da dentina erodida
Keywords: Dentifrices; dentin desensitizing agents; dentin permeability; tooth abrasion; tooth erosion